Fikih Indonesia Hasbi Ash-Shiddieqy - Mulyanti; Asdar, Faizal (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2023)
The Indonesian fiqh framework offered by Hasbi is not an idea of thinking that abandons the thinking tradition of classical scholars with the jargon of reform it offers. The basic framework remains in the main sources of Islamic law, namely the Koran, Hadith, Ijma, Qiyas, Ra‎'yu, and Urf. The notion of Indonesian jurisprudence is also based on the main source of Islamic law, Indonesian jurisprudence must pay attention to the Indonesian contextual situation, so that answers to legal problems do not become foreign products for society. The idea of Indonesian jurisprudence on issues for which there is no legal answer, according to Hasbi, must be decided in a collective ijtihad model which will later provide more comprehensive answers to problems from all perspectives of the problem.